THE APPLICATION OF GAME TECHNOLOGIES IN TEACHING ENGLISH TO ENGINEERING STUDENTS (International Journal of Food and Nutritional Sciences, 2022)
This article explores the use of gaming technology in the English language instruction processfor engineering students. Game technologies in English lessons have long been shown to bean excellent approach to diversify language learning, push students to speak a foreignlanguage, and engage students in an English speaking setting